2022
DOI: 10.1038/s41598-022-08256-3
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray characterization of halide perovskite film by scanning transmission X-ray microscopy

Abstract: Organic–inorganic metal halide perovskites (MHPs) have recently been receiving a lot of attention due to their newfound application in optoelectronic devices, including perovskite solar cells (PSCs) which have reached power conversion efficiencies as high as 25.5%. However, the fundamental mechanisms in PSCs, including the correlation of degradation with the excellent optoelectrical properties of the perovskite absorbers, are poorly understood. In this paper, we have explored synchrotron-based soft X-ray chara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…As mentioned earlier, it is worth noting that the C K-edge and N K-edge could be especially interesting as these belong to the inner shell transitions and could have NEXAFS features (fine structure) that could be very sensitive to chemical functionalities. NEXAFS has been widely used for a variety of materials and has been recently applied to PSC materials to disentangle degradation mechanisms [28,30]. Experimental spectra of various PSC materials were also obtained.…”
Section: Section I Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned earlier, it is worth noting that the C K-edge and N K-edge could be especially interesting as these belong to the inner shell transitions and could have NEXAFS features (fine structure) that could be very sensitive to chemical functionalities. NEXAFS has been widely used for a variety of materials and has been recently applied to PSC materials to disentangle degradation mechanisms [28,30]. Experimental spectra of various PSC materials were also obtained.…”
Section: Section I Discussionmentioning
confidence: 99%
“…However, this could be impractical as spin-coating, often employed in PSC device preparation, will not allow for an X-ray transparent substrate that is necessary for STXM measurements. For bulk information specifically a thin film of appropriate thickness (not a full device), spin-coated or evaporated, can be easily investigated [30,35]. It can be prepared on commercially available Silicon Nitride (Si3N4) windows.…”
Section: Section I Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30–40 Organic–inorganic metal halide perovskites are relatively new. Apart from a paper from our group, 41 very few reports of STXM studies were found in the literature. In Lin et al , 42 the material formation was investigated following the exposure of PbI 2 films to methylammonium iodide and in Li et al 43 the integration of a phenyl ethylammonium cation to the perovskite network was studied.…”
Section: Introductionmentioning
confidence: 98%